A new species of Begonia (Begoniaceae) from South Sulawesi, Indonesia. - Wiriadinata, Harry (Research Center for Biology, 2013)
A new species, Begonia hooveriana Wiriad., is described from Tanah Toraja in South Sulawesi. It belongs to Begonia section Petermannia and brings the total number of Begonia species native to Sulawesi to 43 species.